Recuento de linfocitos T CD4 en pacientes VIH + con neumonía en el servicio de medicina interna Nº. 1 Hospital Nacional Guillermo Almenara Irigoyen (julio 2004 - agosto 2006) - Celiz Nicho, Ana C. (2006)
This series of cases was composed by 27 patients infected by virus of Human Immunodeficiency (HIV), in Acquired Immune Deficiency Syndrome (AIDS) clinical stage ,hospitalized in the Service of Internal Medicine Unit of Infectology of fue National Hospital Guillermo Almenara Irigoyen, because they presented pneumonia, to whom a count of lymphocytes T CD4 (LT CD4) was made using the citometria of flow technique. They were 28 episodes, since a patient was hospitalized on two occasions. Of the 28 episodes, 13 were pneumonia by Pneumocystis jiroveci (PCP) with a LT CD4 average of 72 cells/ml, 11 (39,3 %) was bacterial pneumonias with a LT CD4 average of 120 cells/ml and in 3 (11%) cases the pneumonia was mixed. In our series, 92% of the patients with pneumonia by PCP presented LT CD4 range inferior to 200 cel1s/ml, and in pneumonia bacterial episodes, 9 of them attended with a smaller count of 200 cells/ml.Concluding which the count of LT CD4 is good a predicting factor of disease progression, the most frequent opportunistic infection was caused by PCP and the most frequent bacterial was Klebsiella pneumoniae.